Long-Distance Caregivers' Use Of Supportive Services. Issue 6 (18th August 2022) - Zucchetto, Jillian Minahan; Cimarolli, V.R.; Wylie, M.J.; Falzarano, F.; Horowitz, A.
ABSTRACT: While long-distance caregiving has received increased attention as a unique care experience, prior research has not explored the supportive services used by long-distance caregivers (LDCs) and the factors that predict their supportive service utilization. Using the Andersen Model of Health Care Utilization, the current study sought to: 1) describe the types of supportive services LDCs used and the frequency of usage and 2) identify predisposing, enabling, and need-related factors associated with supportive service use in a sample of LDCs. Participants were recruited from aging services organizations, a national participant registry, professional networks, participant referrals, and an existing pool of research participants. The sample included 304 LDCs who reported on the use of nine supportive services and completed measures assessing depression, caregiver burden, self-rated health, sociodemographic characteristics, and the condition of the care recipient (CR). Fifty percent of LDCs reported no service use. Multiple hierarchical regression analyses demonstrated that younger age, higher caregiver burden, greater depressive symptoms, more time spent helping the CR, and worse CR functional status were significantly related to greater total supportive service use by LDCs. The current study contributes to our understanding of the factors associated with LDCs' supportive service utilization, highlighting the importance of need-related factors.